Self-assessment in Graduate Programs in Education in the Triângulo Mineiro region: an analysis based on CAPES evaluations (2017-2020) (Práxis Educativa, 2025)
This article analyzes how the six Graduate Programs in Education located in the Triângulo Mineiro region, in Minas Gerais, Brazil, have implemented self-assessment, using the evaluation forms of the Brazilian Coordination for the Improvement of Higher Education Personnel (CAPES) from the 2017–2020 quadrennium as a reference. A document analysis was conducted, and the data were processed with the aid of the Iramuteq software. The results reveal that, although efforts have been made to consolidate self-assessment as an institutional practice, challenges remain regarding systematization, alignment with strategic planning, and effective participation of institutional actors. It was concluded that, for its improvement, self-assessment should be understood as a critical and participatory evaluative practice, sensitive to the specificities of each program, and as a formative and strategic tool.Keywords: Evaluative culture. Educational policies. Higher Education.